Treatment of Fish Processing Wastewater using the Multi Soil Layering Method - Maulidah Syakiroh; Rizka Novembrianto (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The wastewater generated by fish-processing industries in Lamongan Regency contains TSS, BOD₅ and COD concentrations that exceed the quality standards specified in East Java Provincial Regulation No. 72/2013. The media in the Multi Soil Layering method consist of a mixture of soil and charcoal, along with a permeable layer. This research aims to analyze the effectiveness of MSL method with variations in soil type, Hydraulic Loading Rate, and sampling time. The results indicate that red soil is the most effective in removing TSS 89,26%, while andosol soil is more efficient in reducing BOD₅ 42,86% and COD 68,33%. The physical, chemical, and mineral properties of each soil type significantly influence pollutant removal performance. Pollutant removal at an HLR of 0,2 m3/m².hour was more optimal compared to 0,4 m3/m².hour, as the lower HLR allows longer contact time between the wastewater and the media in the reactor. Sampling at the 7-hour mark yields optimal efficiency, indicating that the media had not yet reached saturation.